Application of VAT Web Portal on Reporting and Payment of Retail Tax Invoices of Perum Bulog Banyumas - Inggit Zahra Adini; Dona Primasari; Siti Maghfiroh (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The management of retail tax administration at Perum BULOG Banyumas Branch requires a system that is easy to use, precise, and transparent in order to remain intact in tax rules and improve operational efficiency. Research ii was conducted because the previous manual method often caused data input errors, took a long time, and was difficult to monitor directly. To overcome this, Perum BULOG developed and implemented the VAT Web Portal as the main means for reporting and paying tax invoices. The method used is direct observation and descriptive analysis of the portal's workflow, starting from recording transactions, uploading tax documents in standard formats, to automatic data validation. The results of the study show that the VAT Web Portal speeds up the administrative process, maintains consistency of recording, reduces input errors, and facilitates invoice monitoring by officers and related institutions. While these systems are effective, there are obstacles such as reliance on a stable internet connection, the potential for human error when verifying documents, and the need to improve employee digital literacy. The implementation of the VAT Web Portal has succeeded in creating a more efficient, transparent, and consistent tax administration, thereby supporting more modern tax governance. Overall, digital innovation through the VAT Wb Portal provides real benefits for companies and the government in terms of efficiency, accuracy, and tax supervision.